Investigation of Changing Pore Topology and Porosity during Matrix Acidizing using Different Chelating Agents - Umer Shafiq, Mian; Khaled Ben Mahmud, Hisham; Rezaee, M. Reza; Testamanti, Nadia (2017)
Core flooding acidizing experiments on sandstone/carbonate formation are usually performed in the laboratory to observe different physical phenomena and to design acidizing stimulation jobs for the field. During the tests, some key parameters are analyzed such as pore volume required for breakthrough as well as pressure. Hydrochloric acid (HCl) is commonly used in the carbonate matrix acidizing while Mud acid (HF: HCl) is usually applied during the sandstone acidizing to remove damage around the well bore. However, many problems are associated with the application of these acids, such as fast reaction, corrosion and incompatibility of HCl with some minerals (illite). To overcome these problems, chelating agents (HEDTA, EDTA and GLDA) were used in this research. Colton tight sandstone and Guelph Dolomite core samples were used in this study. The experiments usually are defined in terms of porosity, permeability, dissolution and pore topology. Effluent samples were analyzed to determine dissolved iron, sodium, potassium, calcium and other positive ions using Inductively Coupled Plasma (ICP). Meanwhile Nuclear Magnetic Resonance (NMR) was employed to determine porosity and pore structure of the core sample. Core flood experiments on Berea sandstone cores and dolomite samples with dimensions of 1.5 in × 3 in were conducted at a flow rate of 1 cc/min under 150oF temperature. NMR and porosity analysis concluded that applied chemicals are effective in creating fresh pore spaces. ICP analysis concluded that HEDTA showed good ability to chelate calcium, sodium, magnesium, potassium and iron. It can be established from the analysis that HEDTA can increase more amount of permeability as compared to other chelates.